1988
DOI: 10.1152/ajpregu.1988.254.5.r776
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal determinants of sodium excretion in rats with experimental high-output heart failure

Abstract: The present study evaluates the inter-relationship between the alteration in atrial natriuretic factor (ANF) and the renal handling of Na in rats with chronic aortocaval (a-v) fistula, an experimental model of congestive heart failure. Balance studies in these animals showed two distinct patterns of Na excretion: some rats developed progressive Na retention [urinary sodium excretion (UNaV) less than 100 mueq/24 h], whereas others compensated and returned to normal Na balance (UNaV greater than 1,200 mueq/24 h)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
2
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(98 citation statements)
references
References 0 publications
6
89
2
1
Order By: Relevance
“…In addition, this experimental model is characterized by a marked activation of the systemic and intracardiac renin-angiotensin system in proportion to the severity of the disease. 14,15 Indeed, an association between Ang II and induction of MCP-1 gene expression has been documented in rat vascular smooth muscle cells, in aortic tissues of hypertensive rats, and in rat mesangial cells in experimental nephritis. 12,13,27 In vascular smooth muscle cells, the Ang II-induced MCP-1 mRNA accumulation was mediated by the AT 1 receptor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, this experimental model is characterized by a marked activation of the systemic and intracardiac renin-angiotensin system in proportion to the severity of the disease. 14,15 Indeed, an association between Ang II and induction of MCP-1 gene expression has been documented in rat vascular smooth muscle cells, in aortic tissues of hypertensive rats, and in rat mesangial cells in experimental nephritis. 12,13,27 In vascular smooth muscle cells, the Ang II-induced MCP-1 mRNA accumulation was mediated by the AT 1 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported previously. 15 Echocardiography demonstrated that decompensated CHF was associated with a marked degree of cardiac dilatation (Table 2). Figure 1 presents the data on the expression of MCP-1 and rpL32 mRNA, by Northern hybridization, in control and ACF animals at 24 hours, 3 days, and 7 days, respectively.…”
Section: Mcp-1 Binding Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The rats used had 'compensated' for the A-V shunt; those animals that fail to 'compensate' die within the first 7 days after surgery (Winaver et al, 1988). Mean plasma renin activity was 10.3 ± 2.2 ng angiotensin I ml-' h-' in A-V fistula rats (n = 7) and 7.4+ 1.5 ng angiotensin I ml-' h-' in sham-operated controls (n = 9; NS).…”
Section: A -V Fistula Ratsmentioning
confidence: 99%